Early versus late rehabilitation for stroke survivors: A prospective study (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The aim of this study was to examine the optimum time of rehabilitation initiation after stroke in terms of disabilities, mobility and fall risk assessment. Data were collected prospectively at seven tertiary level health care centers in Bangladesh during the 36 months period from 2013 to 2016. All respondents were divided into four groups based on the initiation of rehabilitation as: a) 0-24 hours, b) 25-72 hours, c) 4-7 days and d) 8-60 days. Results show that significant improvement on stroke recovery, disabilities reduction, improvement in mobility restriction and reduction of fall risks in all the four groups but more improvement was observed in 0-24 hour’s group during follow-up after 3 and 12 weeks. On multinomial logistic regression analysis, the independent factors shows the mobility restriction and fall risk were more in the younger patients, male gender, married, hemorrhagic lesion and bilateral stroke.